“Measuring the Immeasurable”—the Effects of Trademark Regimes: a Case Study of Arab Countries - Khoury, Amir H (Journal of Law and Commerce, 2008)
When the law sets out rules and standards it also sets in motion a complex set of mechanisms that determine how the law is implemented and how it functions. Thus, the “law in books” and the “law in action” are, in more ways than one, distinct creatures, separated at birth, leading separate lives. Trademark law is no exception. This research introduces, through data analysis, a method for measuring and assessing the effects of trademark law on countries. In constructing this model I have focused on four Arab countries. However, the model itself is applicable to all countries. Indeed, the comparative data that is presented in this research relates to various countries around the world.